Evaluation of Neurological Remodeling by Moringa Olivera (MO) Extract in PC12 Cell Lines, and Awareness among the Community on the Utilization of MO for Chronic Diseases - Jaiperkash, Ata Ur Rehman, Kiran Khan, Ali Nawaz Bijaarani, Badar Jahan, Syed Zaryab Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The neurodegenerative disorders, including Alzheimer's and Parkinson's disease, affect the elderly population, and there is limited access to pharmacotherapy in Low middle income countries (LMICs) such as Pakistan. The leaves and seed extracts of MO have shown potential activity for neurological remodeling. Hence, the study was designed to assess MOE extract's neurological effects in PC12 cell lines and public KAP on its use for chronic diseases. Methods: It was a mixed method study, In vitro: PC12 cells were cultured in RPMI/Neurobasal medium; extracts (5 200 µg/mL, methanolic) tested for viability (MTT), ROS (DCFDA), LDH release, comet assay (DNA damage) were performed. Pretreatments (2h) preceded H2O2/glutamate insults. In vivo awareness: was evaluated by cross sectional survey (n=385 adults, >30y, chronic disease; stratified from Karachi clinics) by using KAP questionnaire. Interviews (n=35, saturation) explored barriers. Results: In Vitro (RGC/PC12, n=300 wells): M. oleifera extract (MOE) yielded mean viability 91.2±4.5% (100 µg/mL), vs glutamate control 58±3% (p<0.001). The 68% population was aware of MO for chronic diseases; 52% used it and for diabetes 39% reported positive benefits, positive factors: affordability (81%), tradition (47%); distractors: distrust efficacy (36%), interactions (22%). Conclusion: MOE's verified remodeling capacity, juxtaposed against moderate yet barrier laden awareness, positions it as a viable herbal asset for Pakistan's chronic disease crisis. Keywords: Moringa oleifera, neuroprotection, primary neurons, herbal awareness, chronic diseases